2020
DOI: 10.56454/mdvv8543
|View full text |Cite
|
Sign up to set email alerts
|

Termination of Insecticide Applications for Tarnished Plant Bug (Hemiptera: Miridae) Management in Cotton

Abstract: Tarnished plant bug, Lygus lineolaris (Palisot de Beauvois), is the most important insect pest of cotton, Gossypium hirsutum L., in the states of Arkansas, Louisiana, Mississippi, Tennessee, and Missouri. Foliar insecticide sprays are an important tactic within an integrated pest management (IPM) program for this pest which occurs from early flower bud development to cut out, a stage where the plant has reached the capacity for supporting fruiting positions and equivalent to when there are five nodes above the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…No differences in residual effect were found between sulfoxaflor and acephate [49]. Comparably, Siebert et al 2012 [52] demonstrated similar residual efficacy levels at evaluation intervals >6 days after application between sulfoxaflor and acephate against moderately tolerant populations of L. lineolaris in 12 mid-southern U.S. locations from 2008 through 2010. Although, both studies were conducted a decade a part, acephate continually proves to demonstrate highly efficacious for control of L. lineolaris relative to other classes of insecticides regardless of any inherent resistance development.…”
Section: Plos Onementioning
confidence: 99%
“…No differences in residual effect were found between sulfoxaflor and acephate [49]. Comparably, Siebert et al 2012 [52] demonstrated similar residual efficacy levels at evaluation intervals >6 days after application between sulfoxaflor and acephate against moderately tolerant populations of L. lineolaris in 12 mid-southern U.S. locations from 2008 through 2010. Although, both studies were conducted a decade a part, acephate continually proves to demonstrate highly efficacious for control of L. lineolaris relative to other classes of insecticides regardless of any inherent resistance development.…”
Section: Plos Onementioning
confidence: 99%